Pelaksanaan Perjanjian Kredit Pada Lembaga Perkreditan Desa (Lpd) Adat Mengwi - Ni Kadek Putri Candra Wati; Ni Luh Mahendrawati; Ni Made Puspa Sutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2021)
The aim of the presence of the Lembaga Perkreditan Desa Adat Mengwi is to improve the standard of living of the peoples at Mengwi vilage and to support the development of the Mengwi Vil, one of the program carried out by the LPD Mengwi is to distribute funds in the form of credit. In order that the LPD Desa Adat Mengwi not only distribute credit for the local people in Desa Adat Mengwi however it discord with the LPD Desa Adat Mengwi rules. The LPD Desa Adat Mengwi give some previllage to the debtor who is not from Desa Adat Mengwi. In this pasper there are two issues, namely: 1. How the implementation of the credit agreement at Mengwi Village and, 2. How the efforts made by the LPD Mengwi if the debtor is make defaults. This resesarch use the empirical method with the field research and sociological approach. At the implementation of credit agreements at the LPD Mengwi using a standard form of agreement which is contained in the from of an authentic deed and underhanded deed and in the implementation of the loan agreement procedure at the LPD Mengwi is similar to the general credit agreement procedure. The differences is only the terms of the agreement and the settlement efforts that carried out by the the LPD Mengwi as a creditor in case the debtor make default are with the first few stages by giving the first warning letter, if the debtor does not give any respond to the warning letter then there will be be the second warning letter, and if the debtor still does not give any respond there will be the third warning letter. And if there is dtill no respond from the debtor, The LPD Mengwi as a creditor will give a reprimand letter. If there is still does not any respond to the reprimand letter, the guarantee will be seized.